URGENCE OF SAINTIFIC-BASED INQUIRY IMPLEMENTATION IN IMPROVING STUDENT'S CRITICAL THINKING ABILITY - Devi Afriyuni Yonanda; Yuyun Dwi Haryanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Emphasis on learning in the 2013 Curriculum puts forward the development of knowledge, attitudes and skills of students. The Scientific Approach is believed to be a gold platform to produce quality human resources because the learning process is scientific.As we know in Elementary School learning emphasizes on memorization alone where students must memorize all the material that has been learned.Rote learning is certainly not meaningful for students because students will easily forget what they have learned.The ability that students must possess is one of them is critical thinking.Scientific based inquiry needs to be applied in improving students' critical thinking skills, especially in elementary school.Inquiry-based scientific learning models cultivate scientific thinking skills,developing sense of inquiry and students' creative thinking skills.Through writing about inquiry-based scientific inquiry empirically it can be used as an effort to improve students' critical thinking skills.